Original paperAntiplatelet resistance and the role of associated variables in stable patients treated with stenting - Uzun, Fatih; Biyik, Ismail; Akturk, Ibrahim Faruk; Erturk, Mehmet; Yalcin, Ahmet Arif; Surgit, Ozgur; Oner, Ender; Pusuroglu, Hamdi; Birand, Ali (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
Introduction: Nowadays, clopidogrel and acetylsalicylic acid (ASA) have become routinely applied therapies in percutaneous coronary interventions (PCI) with stenting. Aim: Numerous variables can interfere with antiplatelet responsiveness, so we aimed to investigate the role of different variables associated with ASA or clopidogrel resistance in stable coronary artery disease. Material and methods: A total of 207 patients undergoing elective PCI were included in the analysis. All patients received a loading dose of clopidogrel and ASA during PCI procedure and followed by dual antiplatelet therapy. Clopidogrel and ASA resistance were measured by impedance aggregometry method. Results: Of the patients, 19.8% had clopidogrel resistance, 18.8% had ASA resistance, 9.2% had both clopidogrel and ASA resistance, and 71.5% were responsive to both drugs. In multivariate analysis, platelet count, angiotensin receptor blocker (ARB) use, and ASA resistance were independent variables associated with clopidogrel resistance, and clopidogrel resistance was the only variable associated with ASA resistance. In differentiating whether clopidogrel resistance exists or not, optimum ASA aggregometry response cut-off values were specified, and in differentiating whether ASA resistance exists or not, optimum clopidogrel aggregometry response cut-off values were specified. Conclusions : In this study, there was a higher incidence of low responsiveness to ASA when there was a low response to clopidogrel, and vice versa. Angiotensin receptor blocker use, platelet count, and ASA resistance were independent variables associated with clopidogrel resistance. Clopidogrel resistance was the only independent variable associated with ASA resistance. Angiotensin receptor blocker use seems to an independent risk factor for clopidogrel resistance in this study, but this result needs to be verified in other studies.